Neuron-specific modulation of SLC30A10 identifies dopaminergic and glutamatergic neurons as targets of manganese-induced motor disease - Stephanie M. Grant; Ashvini Melkote; Mollie X. Bernstein; Thomas Jursa; Cherish A. Taylor; Steven Hutchens; William Shawlot; Larry S. Zweifel; Rueben A. Gonzales; Donald R. Smith; Somshuvra Mukhopadhyay (Proceedings of the National Academy of Sciences, 2026)
Essential metals accumulate in the basal ganglia at elevated levels and induce incurable motor disease. But, unlike other motor diseases, the neuronal targets of essential metals are unknown, and this fundamental knowledge gap has limited therapeutic progress. Because metal efflux transporters have high specificity, we hypothesized that neuron-specific knockout or knockin (i.e., overexpression) of efflux transporters may alter metal levels in targeted neurons and define the neuronal targets of metal-induced disease. To test this, we focused on manganese (Mn)-induced motor disease, which is a public health problem. We generated six neuron-specific Slc30a10 mouse strains with knockout or knockin of the Mn efflux transporter Slc30a10 in dopaminergic, GABAergic, or glutamatergic neurons. In the knockout strains, SLC30A10 was depleted and Mn levels were elevated in targeted brain regions. However, only dopaminergic- or glutamatergic-, but not GABAergic-, specific knockouts developed motor deficits without Mn exposure. Conversely, in the knockins, SLC30A10 was elevated and the increase in Mn levels after Mn exposure was attenuated in targeted regions. However, only dopaminergic- or glutamatergic-, but not GABAergic-, specific knockins were protected against Mn-induced motor deficits. Dopaminergic-specific Slc30a10 knockouts also exhibited deficits in dopaminergic neurotransmission that were consistent with their motor phenotype. Overall, 1) elevated Mn targets dopaminergic and glutamatergic neurons to induce motor disease, and 2) neuron-specific knockout/knockin of efflux transporters is an effective strategy to isolate the neuronal targets and underlying mechanisms of metal-induced neurological disease.